2019
DOI: 10.1016/j.ijid.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter clinical experience of real life Dalbavancin use in gram-positive infections

Abstract: Dalbavancin, a lipoglycopeptide with prolonged half-life approved for the treatment of acute bacterial skin and soft tissue infections, can be used for the treatment of infections caused by gram-positive bacteria requiring long term treatment such as endocarditis, prosthetic joint infections (PJI) or osteomyelitis. Clinical data are limited in these settings. Objectives: To evaluate indications, safety, tolerability and long-term outcomes of dalbavancin-treated patients.Patients and methods Our multicenter, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
79
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 14 publications
12
79
2
Order By: Relevance
“…The incidence of adverse events observed in this study was similar to that reported in randomized, controlled clinical trials and in real-life reports [7,8,16,19,21]. In our experience, dalbavancin had an excellent safety profile with no significant drug interactions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The incidence of adverse events observed in this study was similar to that reported in randomized, controlled clinical trials and in real-life reports [7,8,16,19,21]. In our experience, dalbavancin had an excellent safety profile with no significant drug interactions.…”
Section: Discussionsupporting
confidence: 88%
“…The main results of our study were that we found good safety of dalbavancin for short-and long-term treatment and high clinical cure rates in acute infection including erysipelas, acute septic arthritis, acute vertebral osteomyelitis, and acute osteomyelitis, but limited treatment success among chronic infections, particularly in cases with insufficient source control. In the last 3 years, several studies reported experiences with dalbavancin use [7,8,19,21]. In the present work, the overall clinical cure rate (64%) under dalbavancin was lower compared with previous reports (84.1% by Bouza et al and 89.5% by Wunsch et al) [8,19].…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Currently, both are approved by the United States Food and Drug Administration only for skin and skin structure infections, but there are increasing reports of successful use in more severe infections including osteomyelitis, bacteremia, and endocarditis. [39][40][41][42] Two studies of dalbavancin in vulnerable populations, including primarily IDU-associated infections, found a somewhat unimpressive 56% and 71% clinical response and success rate, respectively. Without comparison groups, one cannot conclude that patients would have done any better with traditional OPAT or long-term hospitalization.…”
Section: What Is the Best Location For Patients To Receive Antibioticmentioning
confidence: 99%